2004
DOI: 10.1262/jrd.50.493
|View full text |Cite
|
Sign up to set email alerts
|

Regulation Mechanism of Selective Atresia in Porcine Follicles: Regulation of Granulosa Cell Apoptosis during Atresia

Abstract: Abstract. More than 99% of follicles undergo a degenerative process known as "atresia", in mammalian ovaries, and only a few follicles ovulate during ovarian follicular development. We have investigated the molecular mechanism of selective follicular atresia in mammalian ovaries, and have reported that follicular selection dominantly depends on granulosa cell apoptosis. However, we have little knowledge of the molecular mechanisms that control apoptotic cell death in granulosa cells during follicle selection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
140
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 196 publications
(150 citation statements)
references
References 164 publications
(237 reference statements)
6
140
1
3
Order By: Relevance
“…Overexpression of pFADD and pprocaspase-8 induced cell death in the HeLa-K cells. To date, we have investigated the follicular atretic mechanisms of follicular atresia in porcine ovaries [18][19][20][21][22][26][27][28][29][30][31] and have shown that g r a n u l o s a c e l l a p o p t o s i s i s a d o m i n a n t phenomenon in follicular atresia. Therefore, we examined whether overexpressed pFADD and pprocaspase-8 can induce apoptosis in the granulosa cells of human, murine, and porcine origin (KGN, KK1 and JC410, respectively).…”
Section: Apoptosis Inductivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of pFADD and pprocaspase-8 induced cell death in the HeLa-K cells. To date, we have investigated the follicular atretic mechanisms of follicular atresia in porcine ovaries [18][19][20][21][22][26][27][28][29][30][31] and have shown that g r a n u l o s a c e l l a p o p t o s i s i s a d o m i n a n t phenomenon in follicular atresia. Therefore, we examined whether overexpressed pFADD and pprocaspase-8 can induce apoptosis in the granulosa cells of human, murine, and porcine origin (KGN, KK1 and JC410, respectively).…”
Section: Apoptosis Inductivitymentioning
confidence: 99%
“…We previously reported that death ligand/ receptor systems act as initiators of apoptosis in porcine granulosa cells [22,30,31] and showed that an intracellular inhibitory protein, cFLIP, inhibits apoptosis in granulosa cells by binding with the D E D o f F A D D a n d / o r p r o c a s p a s e -8 a n d interrupting the recruitment of procaspase-8 to FADD [29,30]. In the present study, we showed that both the molecular construction and function of apoptotic signaling factors are highly conserved.…”
Section: Apoptosis Inductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Follicular health is regulated by interactions among multiple physiological processes that stimulate cell proliferation and survival or induce apoptotic cell death (Tsafriri & Braw 1984). Apoptosisinducing factors that have been identified in pig granulosa cells include tumor necrosis factor (TNF)-a, Fas ligand (TNF receptor superfamily member 6 or APO1), TNF related apoptosis-inducing ligand (also known as apoptosis-2, APO2), and APO3 (Manabe et al 2004). Whether androgens influenced the actions of one of these factors, other components of the complex intracellular apoptotic pathways, or apoptosis inhibitory mechanisms (survival factors), is not known.…”
Section: Androgens and Follicular Developmentmentioning
confidence: 99%
“…58: [112][113][114][115][116] 2012) I n mammalian ovaries, more than 99% of follicles degenerate at various stages of follicular growth and development [1]. The degeneration is explained, at least in part, by the apoptosis of granulosa cells [2][3][4][5][6]. In porcine ovarian follicles in the early stages of atresia, characteristics typical of apoptosis are observed in scattered granulosa cells, but not in cumulus cells, oocytes or the cells of internal or external thecal layers [7].…”
mentioning
confidence: 99%